Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s10811-017-1157-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for the non-destructive fresh weight determination of filamentous algae for growth rate analysis and dry weight estimation

Abstract: The determination of rates of macroalgal growth and productivity via temporal fresh weight (FW) measurements is attractive, as it does not necessitate the sacrifice of biomass. However, there is no standardised method for FW analysis; this may lead to potential discrepancies when determining growth rates or productivity and make literature comparison problematic. This study systematically assessed a variety of lab-scale methods for macroalgal FW measurement for growth rate determination. Method efficacy was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(43 reference statements)
0
14
0
1
Order By: Relevance
“…For instance, Luo et al [37] reported that Ulva prolifera had higher rates of growth and nutrient uptake than Ulva linza across a range of temperatures, irradiances, and N concentrations, most likely as a result of them having a different thallus morphology. A similar explanation may be valid in this case: Ross et al [13] noted that C. parriaudii grows rapidly outwards in a loose skein, whereas C. coelothrix grows slowly in tightly knit clusters. The denser growth strategy exhibited by C. coelothrix, as opposed to C. parriaudii, will likely enhance the effects of growth-limiting factors, such as self-shading and low nutrient availability within the tightly knit colony, as observed in other members of Cladophoraceae [38,39].…”
Section: Uptake Of Single Nitrogen Sourcesmentioning
confidence: 64%
See 3 more Smart Citations
“…For instance, Luo et al [37] reported that Ulva prolifera had higher rates of growth and nutrient uptake than Ulva linza across a range of temperatures, irradiances, and N concentrations, most likely as a result of them having a different thallus morphology. A similar explanation may be valid in this case: Ross et al [13] noted that C. parriaudii grows rapidly outwards in a loose skein, whereas C. coelothrix grows slowly in tightly knit clusters. The denser growth strategy exhibited by C. coelothrix, as opposed to C. parriaudii, will likely enhance the effects of growth-limiting factors, such as self-shading and low nutrient availability within the tightly knit colony, as observed in other members of Cladophoraceae [38,39].…”
Section: Uptake Of Single Nitrogen Sourcesmentioning
confidence: 64%
“…for FW determination and water chemistry analysis. On each sampling day, FW was determined by placing the biomass into a reticulated spinner (Chef'N Salad Spinner), spinning for 90 s to remove residual water and weighed gravimetrically in an analytical balance (PS-60, Fisher Brand, UK) [13]. Biomass was then returned to its original, corresponding flask and cultivated under the conditions described above.…”
Section: Measurement Of Biomass and Its Constituentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the naive linear regression method to model the EMD baseline (EMD base ). The formula is defined by equation (9).…”
Section: ) Linear Regressionmentioning
confidence: 99%